Malignant mesothelioma in Turkish immigrants residing in Sweden. - Boman, Gunnar; Schubert, Vivianne; Svane, Bertil; Westerholm, Peter; Bolinder, Erik; Rohl, Arthur N.; Fischbein, Alf (Scandinavian Journal of Work, Environment & Health, 1982)
Mesothelioma is a rare neoplasm in the general population, but it is strongly associated with previous asbestos exposure. The endemic occurrence of this disease in two villages in central Turkey has raised the question of whether the inhalation of naturally occurring zeolite dust may also be a factor in the development of mesothelioma. During the past few years a large portion of the inhabitants of one of the two villages of concern has immigrated to Sweden. This report presents three cases of malignant pleural mesothelioma and the results of a chest radiographic survey among these immigrants. Mineralogical analysis of lung tissue specimens from two of the cases revealed the presence of both zeolite and asbestos minerals and therefore suggested a synergistic effect involving both types of minerals. The importance of close medical surveillance of this high-risk population is emphasized, as is the possibility that similar cases appear in other countries because of increased migration.
Keywords: asbestos; environmental exposure; erionite; immigrant; malignant mesothelioma; mesothelioma; Sweden; Turkey; zeikute